Success of Non Operative Treatment in Patients with Spinal Tuberculosis. - Muhammad Mujahid Sharif, Syed Atif Mehmood Kazmi, Masood Mukhtar, Adil Aziz Khan, Bilal Rashid, Sameen Sajjad, Sadaf Abbas, Muhammad Mujahid Sharif, Syed Atif Mehmood Kazmi, Masood Mukhtar, Adil Aziz Khan,Bilal Rashid,Sameen Sajjad,Sadaf Abbas (Journal of Rawalpindi Medical College, 2018)
Background: To determine the success and effectiveness of nonoperative measures in patients with tuberculosis of the spine presenting with or without neurological deficit thus avoiding the surgical intervention. Methods: Seventy (M=20, F=50) patients were included and the study duration was 02 years. Selected patients were advised strict bed rest and antituberculous therapy (ATT) for 18 months. Surgery was done in those patients who presented with severe neurological deficits or non-operative measures did not produce any improvement. Results: Pain was the most common presenting symptom (90%). The motor deficit was seen in 60% and incontinence in 10%. On investigations, end plate erosion was seen in 70% , disc and body involvement in 30% , paravertebral abscess in 40 %. Majority of the patients (70%) patients were treated successfully with non-operative measures. Conclusion: Results are satisfactory in patients who have advised strict bed rest and ATT for 18 months. This helps in reducing the rate of surgical intervention in patients with spinal tuberculosis. It signifies the importance of ATT as it is the mainstay of treatment in spinal tuberculosis.